Pemberdayaan Taman Monumen 45 Banjarsari sebagai Ruang Publik Berbasis Smart Inclusive Garden - Azahra Qanita Aisylabiba; Muhammad Hafizh Arlianto; Aubry Fairuza Akifa Prabowo (Badan Riset dan Inovasi Daerah Kota Surakarta, 2025)
The empowerment of Taman Monumen 45 Banjarsari as a public space based on the Smart Inclusive Garden concept aims to enhance the park’s accessibility, comfort, and sustainability as an inclusive green open space. This study identifies several challenges faced by the park, including the lack of inclusive facilities, suboptimal waste management, and limited community engagement. Through the implementation of smart and environmentally friendly technologies, the Smart Inclusive Garden concept is proposed to transform the park into not only a recreational area but also an educational and interactive space. Proposed innovations include solar-powered playground equipment, smart gazebos, and digital information systems that promote historical and environmental literacy. The integration of such technologies will also facilitate waste management and energy efficiency. By involving the government, local communities, academics, and the private sector, Taman Monumen 45 Banjarsari is expected to transform into a sustainable and inclusive public space that supports the achievement of the Sustainable Development Goals (SDGs) and serves as a model for other public spaces in the region.